Infection Control Knowledge, Attitudes, and Practices among Students of Public Dental Schools in Egypt - Christina El-saaidi (International Journal of Environmental Research and Public Health, 2021)
In developing countries such as Egypt, the risk of blood-borne diseases such as human immunodeficiency virus, hepatitis B virus, and hepatitis C virus is high for healthcare workers. To evaluate infection control knowledge, attitudes and practices, as well as the associated risk of percutaneous infection among dental students, a cross-sectional study was conducted in four Egyptian public dental schools in 2016. A total of 1776 students received an anonymous questionnaire on infection control knowledge, attitudes, and practices and the occurrence of needle and sharps injuries; 1067 (60.1%) completed the questionnaire. Third- (pre-clinical), fourth- (junior-clinical), and fifth-year (senior-clinical) students comprised 44.2%, 15.6%, and 40.2%, respectively. Although the majority of the students reported good attitudes and practices for infection control, knowledge scores were generally low. Female students scored higher on self-protection and sterilization practices than did male students, and the fourth-year students showed significantly higher scores for infection control practice than did the fifth-year students. In multivariate analysis, higher scores for all infection control practices were associated with higher scores for attitudes towards infection control and fewer (1–3) needle injury experiences. Although an alarming proportion had experienced needle or sharps injuries during clinical training, around 30% of the students had not received a complete hepatitis B vaccination. Future infection control education should introduce refresher training before graduation that focuses on injury prevention and post-exposure protocols. Additionally, introducing safer products and clinical procedures is highly recommended to minimize the risk of injuries during clinical practice for dental students in Egypt.